EFFECT OF SOCIOECONOMIC STATUS ON CLEFTS OF LIP, ALVEOLUS AND PALATE IN POPULATION BELONGING TO THE EASTERN PART OF INDIA - Prerana Aggarwal; Biswarup Banerjee; Parthapratim Gupta; Asis Kumar Datta (National Journal of Medical Research, 2014)
Objective: The socioeconomic status of parents, specially the one in which the mother is brought up, affects her general health. This in turn can lead to the birth of a child with congenital abnormalities. A non-syndromic cleft of the lip, alveolus or palate (CLAP) is one of the common possibilities. Our objective was to explore association between socioeconomic status and occurrence of CLAP.